2023
DOI: 10.2196/preprints.49647
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicians’ and Patients’ Expectations From Digital Agents for Consultations: Interview Study Among Physicians and Patients (Preprint)

Abstract: BACKGROUND Physicians are overwhelmed by administrative tasks and spend too little time counseling patients, hampering health literacy, shared decision-making, and adherence to treatment. OBJECTIVE Do digital agents built on fast-evolving generative AI, such as ChatGPT, have the potential to improve healthcare counseling? We sought answers by asking patients and physicians for their opinions on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The problem identification and motivation activity is based on related work and two studies conducted by us [4,15]. Both studies are based on in-depth interviews [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The problem identification and motivation activity is based on related work and two studies conducted by us [4,15]. Both studies are based on in-depth interviews [16].…”
Section: Methodsmentioning
confidence: 99%
“…In a prior study [4], we identified the following core concepts for a functional architecture specifying systems that integrates EMRs with mHealth applications: (1) Patientcenteredness, (2) support of physician-patient relationship and collaboration, (3) adaptive interventions, and (4) integration of mHealth apps into medical workflows and EMRs. We use these concepts to assess existing architectures [5,6].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation